A Case Study on Pemphigus Vulgaris - Nagaraju, Bandaru; Ramu, Anne; vidhyadhara, Suryadevara; Gunasree, Hanumanula; Kumar, Chadalavada Arun (Indian Journal of Pharmacy Practice)
Pemphigus vulgaris is a rare chronic blistering skin disease. It is classified as a type II hypersensitivity reaction, with the formation of antibodies against desmosomes, components of the skin that function to keep certain layers of skin bound to each other. As desmosomes are attacked, the layer of skin separate and the clinical picture resembles a blister. Over time the condition inevitably progresses without treatment lesions increase in size and distribution throughout the body, behaving physiologically like a severe burn.
Keywords: Vulgaris; Blistering; Hypersensitivity; Desmosomes; Lesions